A new model for the drying of mannitol-water droplets in hot air above the boiling temperature - Grosshans, Holger; Gutheil, Eva (Powder technology, 2016)
The drying of bi-component droplets may be divided into five stages, including initial droplet heating and evaporation (stage I), quasi-equilibrium evaporation of the volatile component (II), solid layer formation (III), boiling (IV) and drying (V), as suggested by Nešić and Vodnik in 1991. If the drying temperature is below the boiling temperature of the involved liquid, the boiling stage does not occur. For this situation, a numerical model for spherically symmetric droplets has been developed recently, taking into account the solid layer formation and its resistance on the evaporation process. In the present study, an extension of this model is proposed to include the droplet drying in a gas environment above the boiling temperature, where all five stages occur. The results of numerical simulations are compared to experimental data, where the drying of acoustically levitated mannitol-water droplets in hot gas is studied. The numerical results show that the model captures the principal droplet/particle temperature evolution with time suggested in the literature. When the pressure inside the particle causes higher structural stress than the solid layer can sustain, a crack occurs, enabling the vapor inside the particle to escape through this crack, which leads to a decrease of both pressure and temperature inside the particle. After the pressure adjusts to that of the surrounding air, the crack closes and heals, which, in turn, leads to pressure increase inside the particle, and this cycle may repeat. The numerically predicted temporal development of the size of the particle surface area is validated by comparison with experimental data obtained by shadowgraphy. The new model accurately predicts the experimentally observed final particle size, which is highly affected by the particle expansion during the boiling stage, as well as its porosity. The present approach constitutes a major step towards the tailoring of particles through adjustment of the drying conditions in spray drying processes.